Patterns of conservation and change in honey bee developmental genes. - Dearden, P; Wilson, M; Sablan, L; Osborne, P; Havler, M; McNaughton, E; Kimura, K; Milshina, N; Hasselmann, M; Gempe, T; Schioett, M; Brown, S; et al. (2006)
The current insect genome sequencing projects provide an opportunity to extend studies of the evolution of developmental genes and pathways in insects. In this paper we examine the conservation and divergence of genes and developmental processes between Drosophila and the honey bee; two holometabolous insects whose lineages separated approximately 300 million years ago, by comparing the presence or absence of 308 Drosophila developmental genes in the honey bee. Through examination of the presence or absence of genes involved in conserved pathways (cell signaling, axis formation, segmentation and homeobox transcription factors), we find that the vast majority of genes are conserved. Some genes involved in these processes are, however, missing in the honey bee. We have also examined the orthology of Drosophila genes involved in processes that differ between the honey bee and Drosophila. Many of these genes are preserved in the honey bee despite the process in which they act in Drosophila being different or absent in the honey bee. Many of the missing genes in both situations appear to have arisen recently in the Drosophila lineage, have single known functions in Drosophila, and act early in developmental pathways, while those that are preserved have pleiotropic functions. An evolutionary interpretation of these data is that either genes with multiple functions in a common ancestor are more likely to be preserved in both insect lineages, or genes that are preserved throughout evolution are more likely to co-opt additional functions.